Slow Metabolism–Driven Amplification of Hepatic PPARγ Agonism Mediates Benzbromarone‐Induced Obesity‐Specific Liver Injury - Guanting Li; Yourong Hu; Han Zhao; Ziyu Peng; Xin Shang; Jia Zhang; Kunxin Xie; Meiwei Li; Xiaohang Zhou; Qinyao Zhou; Kai Li; Fang Zhou; et al. (Advanced Science)
Abstract Obesity and nonalcoholic fatty liver disease (NAFLD) are established risk factors for drug‐induced liver injury (DILI). The previous study demonstrates that benzbromarone (BBR), a commonly prescribed pharmaceutical agent for managing gout and hyperuricemia, exacerbates hepatic steatosis and liver injury specifically in obese individuals. However, the precise mechanism underpinning this adverse effect remains incompletely elucidated. Given the significance of BBR and its analogs in anti‐gout/hyperuricemia drug discovery, elucidating the mechanism by which BBR exacerbates obesity‐specific DILI warrants further investigation. In this study, through a combined multi‐omics, pharmacological, and pharmacokinetic approaches, it is found that BBR‐induced obesity‐specific DILI is primarily through the potentiation of peroxisome proliferator‐activated receptor gamma (PPARγ) signaling pathways. Further in vivo and in vitro pharmacokinetic analyses reveal that obese db/db mice exhibited a diminished capacity to metabolize BBR in their livers. This reduction leads to prolonged retention of BBR, subsequently resulting in chronic and sustained hepatic PPARγ agonism. This study demonstrates that a slow metabolism‐driven amplification of hepatic PPARγ agonism mediates BBR‐induced obesity‐specific hepatic steatosis and subsequent DILI, which also emphasizes the importance of the reduced hepatic drug metabolism capacity in patients with obesity or pre‐existing NAFLD in both clinical practice and drug discovery processes.